2010
DOI: 10.1002/ajh.21667
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of specific microRNA and their targets in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) the most common acute leukemia in adults is characterized by various cytogenetic and molecular abnormalities. However, the genetic etiology of the disease is not yet fully understood. MicroRNAs (miRNA) are small noncoding RNAs which regulate the expression of target mRNAs both at transcriptional and translational level. In recent years, miRNAs have been identified as a novel mechanism in gene regulation, which show variable expression during myeloid differentiation. We studied miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
105
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 56 publications
15
105
1
1
Order By: Relevance
“…In the case of miR-125b, it will also be of interest to assess whether it transforms HSCs or a committed myeloid progenitor and to characterize secondary mutations that may assist in this process. Many of the miRNAs identified in our study, including miR125b, miR-155, miR-126, miR-196b, and miR-99a, have been shown to be dysregulated in different subsets of AML (31). Because we have shown functional relevance for many of these HSC miRNAs in vivo, including the abilities of miR-155 (16) and now miR-125b to trigger aggressive MPDs and myeloid leukemia, respectively, therapeutic targeting of this subset may be effective in combating hematopoietic cancers.…”
Section: Discussionmentioning
confidence: 65%
“…In the case of miR-125b, it will also be of interest to assess whether it transforms HSCs or a committed myeloid progenitor and to characterize secondary mutations that may assist in this process. Many of the miRNAs identified in our study, including miR125b, miR-155, miR-126, miR-196b, and miR-99a, have been shown to be dysregulated in different subsets of AML (31). Because we have shown functional relevance for many of these HSC miRNAs in vivo, including the abilities of miR-155 (16) and now miR-125b to trigger aggressive MPDs and myeloid leukemia, respectively, therapeutic targeting of this subset may be effective in combating hematopoietic cancers.…”
Section: Discussionmentioning
confidence: 65%
“…25 These results suggest that the miR-125b-2 polycistron may be regulated by posttranscriptional mechanisms in early hematopoiesis. Similar to miR-125b-2, miR-99a was found to be upregulated in AMKL cell lines, 61 in AMLs with the translocation AML1/ETO, 41 in APL involving PML/RARA 44 and in resistant ALLs. 49 However, in more differentiated B-cells, a correlation in the expression level could not be demonstrated between miR-125b-2 and miR-99a or let-7c.…”
Section: The Role Of the Cluster Mir-125b-2 Mir-99a And Let-7c In Lementioning
confidence: 78%
“…The expression levels varied depending on the methodologies used for expression and controls, but are generally up to 20-fold compared with normal BM. These malignancies include myelodysplastic syndrome involving the del (5q), 39,40 AMLs harboring the AML1/ETO translocation, 41 AMLs associated with the FLT3 mutation, 41 a few cases of chronic myelogenous leukemia, myeoproliferative neoplasms 42 and acute promyelocytic leukemia 43,44 (Table 1). The most investigated hematopoietic malignancy with increased expression of miR-125b is acute megakaryocytic leukemia associated with Down's syndrome (DS).…”
Section: Mir-125b In Myeloid Malignanciesmentioning
confidence: 99%
“…30,31 Others have correlated miRNA expression changes with leukemia subtype, cytogenetic profile and molecular alterations. 30,[32][33][34] …”
Section: Mirnas In Blood-related Cancersmentioning
confidence: 99%